Economics of food grain distribution : (Asian Productivity Organization, 1976)
This book introduce about food situation in Asia and the pacific major supply and demand problem for grains. Food grain market structure, price structure and markrting costs, performance of private trade and cooperatives. Effects of agricultural price policy on governmant, producer's and consumers' expenditure.